Physiological reactions of the cardiovascular system in conditions of vestibular irritation in tennis players - Zavalishina, S. Yu.; Kachenkova, E. S.; Zbrueva, Y. V.; Germanov, G. N. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the reaction of the cardiovascular system to vestibular irritation in tennis players with different lengths of sports experience.